An Unusual Case of Syringohydromyelia Presenting with Neurogenic Bladder - Geljic, Antonella; Abdovic, Slaven; Stampalija, Fran; Loncar, Lana; Tripalo, Batos A.; Cuk, Martin (European Journal of Pediatric Surgery Reports, 2019)
We report the case of a 4-year-old boy who first presented with acute pyelonephritis at the age of 6 months. Diagnostic workup revealed high-grade bilateral vesicourethral reflux (VUR). At the age of 18 months, a bulking agent was used to treat bilateral VUR. Since the VUR persisted, an open bilateral Lich-Gregoir procedure was done at the age of 3 years. Immediately after surgery, he developed acute urinary retention with hydronephrosis that resolved with the placement of dwelling urinary catheter. After removal of the catheter urinary retention relapsed so placement of suprapubic urinary catheter was indicated since he did not have sensory loss. He was started with tamsulosin (α − 1-blocker) and prophylactic antibiotics. Urodynamics were performed and suggested bladder outlet obstruction. On the basis of previous urethroscopy and the absence of neurological sequelae, the differential diagnosis of Hinman syndrome was made. After removal of the suprapubic catheter, clean intermittent catheterization was started and α-blocker continued. However, magnetic resonance imaging of the brain and the spinal cord revealed syringohydromyelia extending from thoracic spine (Th5) to conus medullaris with 6 to 7 mm in diameter. Electromyoneurogram was normal. After a follow-up of 3 years, the hydronephrosis has resolved. The patient is on clean intermittent catherization and has no urinary tract infections.
Keywords: neurogenic bladder; syringohydromyelia; vesicourethral reflux